A noite do Cordeiro - Gruber, Daniel Fernando (2019)
This work is divided into two parts, one fictional and one essayistic. The first part presents the unpublished novel A Noite do Cordeiro, which investigates the power relations in the Brazilian colonial period, based on belief and disbelief, fanaticism and persecution, having as the background of the Portuguese Inquisition in Bahia in 17th century and the obsession with the stereotype of the witch disseminated during that period. The second part, entitled “Poética do medo do escuro”, aims to reflect the creation of the novel, guided by the elements that constitute it as a thriller, with a view to building the effect of fear and tension in the form as it appears in gothic and horror literature. Combining fiction and reflection, the work intends to demonstrate how the use of the elements of fear serve as a historical setting narrative to make it reflect on contemporary anguish.